PERFORMANCE EVALUATION OF RECLAIMED ASPHALT PAVEMENT MIXED WITH MULTI-LAYER PLASTIC WASTE FOR SUSTAINABLE URBAN INFRASTRUCTURE - Thoriqul Huda; Ahyudanari Ervina; Widyatmoko Iswandaru; Habib Noor Zainab (Universitas Trisakti, 2025)
Aim: This study aimed to evaluate the performance of 30% and 50% Reclaimed Asphalt Pavement (RAP) mixtures incorporating polymer as a recycling agent. Multi-layer Plastic (MLP) waste was used along with the coupling agent lignin to improve compatibility between the materials. Methodology and results: RAP was processed to separate the aged binder from the reclaimed aggregate, and both components were characterized by physical analysis. The results showed that the presence of aged asphalt in RAP affected the gradation consistency and decreased the bulk density of the RAP aggregate. The Asphalt Concrete-Wearing Course (AC-WC) specification was applied, and analyses were completed based on Marshall mix design parameters. The results indicated an increase in the stability values of the RAP mixtures by up to 15%. This condition was accompanied by increased volumetric parameters, causing the 50% RAP mixture to exceed the allowable threshold values. The recycling agent provided better compatibility, resulting in a decrease in the void percentage of the 30% RAP mixture. The Residual Strength Index (RSI) analysis demonstrated that the recycled mixtures exhibited better resistance to moisture, particularly the 30% RAP mixture, which showed more than a 10% increase in the RSI value. Conclusion, significance and impact study: The recycling agent is crucial in reducing the porosity and air voids in mixtures containing RAP. Increased adoption of mixtures incorporating solid construction waste, such as RAP, can contribute to the conservation of natural resources. Substituting new asphalt and aggregates with recycled materials will help achieve sustainability goals in road construction projects.